2023
DOI: 10.3390/medicina59122083
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the N-Terminal of the Prohormone Brain Natriuretic Peptide in Predicting Acute Kidney Injury Requiring Renal Replacement Therapy in Patients Undergoing Heart Valve Surgery

Piotr Duchnowski,
Witold Śmigielski

Abstract: Background and Objectives: By definition, acute kidney injury (AKI) is a clinical syndrome diagnosed when the increase in serum creatinine concentration is >0.3 mg/dL in 48 h or >1.5-fold in the last seven days or when diuresis < 0.5 mL/kg/h for a consecutive 6 h. AKI is one of the severe complications that may occur in the early postoperative period in patients undergoing heart valve surgery, significantly increasing the risk of death. Early implementation of renal replacement therapy increases the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…During follow-up, three patients died, due to cardiac failure, multiorgan failure (including renal failure), and renal failure, respectively. Research conducted on patients undergoing valve replacement suggested that elevated preoperative NT-proBNP levels may correlate with an increased risk of postoperative acute kidney injury [ 25 ]. Another study indicated that cardiac biomarkers, including NT-proBNP, offer prognostic insights, including mortality prediction, in patients with PAD [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…During follow-up, three patients died, due to cardiac failure, multiorgan failure (including renal failure), and renal failure, respectively. Research conducted on patients undergoing valve replacement suggested that elevated preoperative NT-proBNP levels may correlate with an increased risk of postoperative acute kidney injury [ 25 ]. Another study indicated that cardiac biomarkers, including NT-proBNP, offer prognostic insights, including mortality prediction, in patients with PAD [ 26 ].…”
Section: Discussionmentioning
confidence: 99%